Legal position of management in Republic of Slovenia - Senčur Peček, Darja (Anali PAZU, 2022)
The author deals with definiton of notion of management (managerial staff), discusses a present legal regulation of employment position of management in Republic of Slovenia and their participation in management. The author exposes some imperfections of present legal regulation and proposes possible solutions.
Keywords: executives; workers with special powers and responsibilities; employment; fixed-term employment contract; participation in management